La regina del teatro italiano e il ‘Napoleone della fotografia’. L’incontro tra Adelaide Ristori e Napoleon Sarony - Marianna Zannoni (Drammaturgia)
This essay aims to provide a cross-section of the 19th century photography through the lucky encounter between Adelaide Ristori and the American Napoleon Sarony, who portrayed the actress on various occasions years apart. This historical reconstruction begins with an analysis of the photographs of the actress as Marie Antoinette, the protagonist of Paolo Giacometti’s historical drama of the same name. The prints, thoroughly preserved by Ristori in her archive, bear the signature of one of the most esteemed authors of international photography, who has gone down in history as the ‘Napoleon of photography’.